The Urgency of Legal Protection For Indonesian Illegal Migrant Workers From the perspective of Sharia Economic Law - Mohammad Reza Fachruddin; Rodiyah, Rodiyah; Dewi Sulistianingsih (The Indonesian Journal of International Clinical Legal Education, 2025)
This study examines the legal protection of illegal Indonesian migrant workers, who are considered both as lawbreakers and victims of exploitation, in the context of compliance with Indonesian migrant worker and immigration laws and the protection of human rights based on Islamic law. Using normative legal research, the study analyses the imbalance between Law No. 18/2017, which limits protection for migrant workers who have legal documents, and the 1990 CMW Convention and the 2000 Palermo Protocol, which guaranty the basic rights, regardless of the legal status. The results of the study reveal that the pros and cons regarding illegal procedural Indonesian migrant workers are in substance to the violation of the law. From an Islamic law perspective, this issue needs to be addressed and a solution sought by updating Law Number 18 of 2017 so that there is no difference between official and unofficial Indonesian migrant workers. This is in line with the maqashid syari'ah in Islamic law, the 1990 CMW Convention and the 2000 Palermo Protocol.